Oil Prices and GCC Stock Markets : New Evidence from Smooth Transition Models - Ben Cheikh, Nidhaleddine (IMF Working Papers; Working Paper, 2018)
Our paper examines the effect of oil price changes on Gulf Cooperation Council (GCC) stock markets using nonlinear smooth transition regression (STR) models. Contrary to conventional wisdom, our empirical results reveal that GCC stock markets do not have similar sensitivities to oil price changes. We document the presence of stock market returns' asymmetric reactions in some GCC countries, but not for others. In Kuwait's case, negative oil price changes exert larger impacts on stock returns than positive oil price changes. When considering the asymmetry with respect to the magnitude of oil price variation, we find that Oman's and Qatar's stock markets are more sensitive to large oil price changes than to small ones. Our results highlight the importance of economic stabilization and reform policies that can potentially reduce the sensitivity of stock returns to oil price changes, especially with regard to the existence of asymmetric behavior.